Pengaruh Dewan Direksi, Komisaris Non Independen, dan Kepemilikan Manajerial pada Kinerja Perusahaan Manufaktur di BEI - Dany Yadnyapawita, I Made; Aryista Dewi, Ayu (E-Jurnal Akuntansi; Vol 30 No 8 (2020)DO - 10.24843/EJA.2020.v30.i08.p07, 2020)
The purpose of this study was to determine the effect of the Board of Directors, Non Independent Commissioners, and Managerial Ownership to Manufacturing Company Performance on the Indonesia Stock Exchange. This research was conducted at food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in the period 2014-2018. Data analysis uses multiple linear regression to determine the relationship between more than two variables. Based on the results of the study stated the Board of Directors statistically has no significant effect to company performance (ROA). Non independent commissioners statistically has no effect to company performance (ROA), Managerial ownership has no statistically significant effect to company performance (ROA). Keywords: Board Of Directors; Independent Commissioners; Managerial Ownership; Company Performance.